2021
DOI: 10.1038/s41588-021-00970-4
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of a genetic module essential for assigning left–right asymmetry in humans and ancestral vertebrates

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 91 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…The direction of asymmetry might result from intracellular or cytoplasmic chirality that biases the production of one asymmetric morph over the other one by influencing the side of expression of certain morphogens (e.g. [66][67][68][69][70]). Under this scenario, subcellular asymmetries might favour the shift of thresholds consistently towards one direction, resulting in one morph having higher probability of fixation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of asymmetry might result from intracellular or cytoplasmic chirality that biases the production of one asymmetric morph over the other one by influencing the side of expression of certain morphogens (e.g. [66][67][68][69][70]). Under this scenario, subcellular asymmetries might favour the shift of thresholds consistently towards one direction, resulting in one morph having higher probability of fixation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Similar post-transcriptional regulatory mechanisms generate LR asymmetry of Dand5 homologs in fish and frog (Hojo et al, 2007;Schweickert et al, 2010;Maerker et al, 2021). A recent phylogenetic study comparing vertebrates with motile cilia in their LRO versus those without cilia elucidated a set of 5 proteins lost in animals without a ciliated LRO (Szenker-Ravi et al, 2022).…”
Section: The Left-right Organizermentioning
confidence: 95%
“…Analyses of one of these proteins, a metalloprotease termed ciliated left right organizer metallopeptidase (CIROP), revealed that it functions as an upstream factor necessary for Dand5 asymmetry in mouse, frog and fish embryos, and that CIROP mutations are found in human laterality patients (Szenker-Ravi et al, 2022). How flow is sensed by LRO cells to asymmetrically impact CIROP, Bicc1, and potentially other regulators remains unclear.…”
Section: The Left-right Organizermentioning
confidence: 99%
“…This evokes the concept of ‘functional modules’ where expression of a group of genes are tightly coordinated to act in the same developmental process ( Niehrs and Pollet, 1999 ; Szenker-Ravi et al, 2022 ), featuring essential gamete characteristics. For example, a module of meiosis contributes to halving the genome, whereas a module of folliculogenesis and spermatogenesis renders gametes feminized or masculinized, respectively.…”
Section: Model: Functionally Distinct Modules Integrate Gametogenesismentioning
confidence: 99%